Postoperation of preauricular fistula cellulitis caused by methicillin-resistant staphylococcus aureus infection - Haiyue Tian; Cuiping Zhang (Journal of Otology, 2018)
A one-year-old baby girl with one-month history of recurrent pus fluid exuding from her left preauricular sinus orifice, who failed multiple courses of surgical drainage of the abscess and persistent debridement for the wound, presented with MRSA infection. The patient was treated with linezolid for three days. Her pain and paresthesia resolved, and C-reactive protein decreased to normal. Keywords: Preauricularsinus, Surgery, Overuse antibiotics, Methicillin-resistant staphylococcus aureus, Cellulitis